1997
DOI: 10.1002/jlb.62.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to ICAM-1 preserves postischemic blood flow and reduces infarct size after ischemia-reperfusion in rabbit

Abstract: Abstract:Neutrophils are pivotal in the pathogenesis of reperfusion injury leading to myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 36 publications
0
35
0
4
Order By: Relevance
“…PMN inhibition was achieved by leukodepletion using neutrophil antiserum (Kin et al, 2006), or by antibodies targeting adhesion molecules such as P-and E-selectins (Lefer et al, 1994), CD11/CD18 (Ma et al, 1991), intercellular adhesion molecule-1 (Ma et al, 1992;Ioculano et al, 1994;Zhao et al, 1997Zhao et al, , 2003, or platelet/endothelial cell adhesion molecule-1 (Gumina et al, 1996). These strategies provided up to ϳ50% reduction in infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…PMN inhibition was achieved by leukodepletion using neutrophil antiserum (Kin et al, 2006), or by antibodies targeting adhesion molecules such as P-and E-selectins (Lefer et al, 1994), CD11/CD18 (Ma et al, 1991), intercellular adhesion molecule-1 (Ma et al, 1992;Ioculano et al, 1994;Zhao et al, 1997Zhao et al, , 2003, or platelet/endothelial cell adhesion molecule-1 (Gumina et al, 1996). These strategies provided up to ϳ50% reduction in infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, is associated with increased expression of adhesion molecules including ICAM and VCAM (46,47), which can be blocked by proteasome inhibitors (47) or other compounds capable of inhibiting NF-κB activity (40). Furthermore, inhibition of proteasome-mediated IκBα degradation (48) or adhesion molecule expression has been shown to reduce significantly ischemia-reperfusion injury (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the inflammatory response that accompanies an acute MI contributes to the pathogenesis of lethal myocardial reperfusion injury or whether it is a reaction to the acute myocardial injury (42). Although experimental studies have reported significant reduction of MI with therapeutic strategies designed to inhibit the inflammatory process at the time of myocardial reperfusion using antibodies against cell-adhesion molecules (43)(44)(45) and the inhibition of complement activation (46), corresponding clinical studies using this therapeutic approach have been largely negative (47)(48)(49).…”
Section: Figurementioning
confidence: 99%